ECO-INNOVATION FOR A SUSTAINABLE FUTURE - RATIU Mariana (Annals of the University of Oradea: Fascicle of Textiles, Leatherwork, 2014)
Eco-innovation is any form of innovation resulting in or aiming at significant and demonstrable progress towards the goal of sustainable development, through reducing impacts on the environment, enhancing resilience to environmental pressures, or achieving a more efficient and responsible use of natural resources. States and governments of the world, different institutions and organizations actively involved and aware in public policies, strategies and actions, reaffirm their commitments and reassess actions in order to achieve a truly sustainable development. In the common vision and the resolutions and other documents of the United Nations Conference on Sustainable Development, Rio+20, the words "environment", "innovation", "green economy" appear very often and almost always along the same context, to achieve the objectives of the sustainable development. The objectives of EU's Europe 2020 strategy for smart, sustainable and inclusive growth, are being implemented through a number of Flagship Initiatives addressing the main challenges, like “Innovation for a sustainable Future - The Eco-innovation Action Plan (EcoAP)”. Eco-innovation Observatory developed the Eco-Innovation index, the first tool to assess and illustrate eco-innovation performance across the EU Member States. Like in all fields, in textiles and leather field, eco-innovation is present and there are a lot of tools available that measure environmental damage and help manufacturers and brands become more sustainable. Eco-innovation is not just a trendy concept but a reality and a necessity nowadays, a way to achieve a sustainable future for ourselves and future generations.